Friend Or Foe In Gary Winick's Bride Wars (2009): An Individual Psychological Approach - Basith, Abdul (2012)
The study is to reveal how the friendship relation of the major characters, Emma Allen and Olivia Liv Lerner. The objective of the study is to analyze the movie based on the structural analysis and the individual psychological approach. This study is a qualitative study. The object of the study is Gary Winick's Bride Wars. The data sources are divided into two, namely primary data source and secondary data source. In collecting the data, the writer watches the movie and uses library research by collecting and selecting the appropriate data from many sources. The technique of the data analysis, the writer uses descriptive technique. After analyzing the movie of Gary Winick's Bride Wars, the writer concluded that there are several aspects of individual psychological approach of the major character. The aspects consist of fictional finalism, striving for superiority, inferiority feeling, style of life, social interest, and creative power. Emma Allen and Olivia Liv Lerner have some efforts to reach their fictional goal. They want to marry on Plaza hotel on June eventhough they must fight each other after they get the same date of wedding; the facts above show that the final goal of Emma Allen and Olivia Liv Lerner guides them to be more creative to make their dream come true.